2022
DOI: 10.1155/2022/9595184
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Adenoviral Load for Bronchial Mucus Plugs Formation in Children with Adenovirus Pneumonia

Abstract: Background. The study aimed to explore risk factors for bronchial mucus plugs (BMP) formation in children with adenovirus (AdV) pneumonia. Methods. A retrospective study was conducted on children with AdV pneumonia who underwent bronchoscopy from January 2019 to December 2019. Children were divided into the BMP group and the control group, depending on whether BMP was formed or not. The clinical information and treatment proposals of the two groups of children were counted and analyzed via multiple logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Besides, pooled results of 6 studies ( 18 , 20 , 23 , 32 , 35 , 36 ) indicated that the pretreatment LDH was significantly higher in children who developed PIBO as compared to those who did not (SMD: 0.47, 95% CI: 0.09 to 0.84, p = 0.02, I 2 = 80%; Figure 2B ). Sensitivity analysis by omitting one study at a time also showed consistent results (SMD: 0.23 to 0.57, p all < 0.05).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Besides, pooled results of 6 studies ( 18 , 20 , 23 , 32 , 35 , 36 ) indicated that the pretreatment LDH was significantly higher in children who developed PIBO as compared to those who did not (SMD: 0.47, 95% CI: 0.09 to 0.84, p = 0.02, I 2 = 80%; Figure 2B ). Sensitivity analysis by omitting one study at a time also showed consistent results (SMD: 0.23 to 0.57, p all < 0.05).…”
Section: Resultsmentioning
confidence: 93%
“…The treatments during hospitalization were only reported in eight studies ( 15 , 18 , 20 , 22 , 23 , 34 – 36 ), which included symptomatic and supporting treatments, oral prednisone and intravenous steroids, intravenous immunoglobulin, antiviral ribavirin, and respiratory support if necessary ( Table 1 ). The follow-up durations were within hospitalization in most of the included studies, while others were with a follow-up duration of 1 month ( 36 ), 3 months ( 20 , 35 ), and 12 months ( 18 , 23 , 32 ). As for the outcomes reported, 14 studies reported the difference of LDH level at baseline between children with severe and non-severe ADVP ( 14 , 16 , 17 , 19 , 21 , 24 – 31 , 33 ), 6 studies reported the difference of LDH level at baseline between children who developed and did not develop PIBO ( 18 , 20 , 23 , 32 , 35 , 36 ), and three studies reported the association between LDH admission and in-hospital mortality of children with ADVP ( 15 , 22 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations